Kemampuan Berpikir Kritis Siswa SMP dalam Menyelesaikan Asesmen Kompetensi Minimum Numerasi Ditinjau dari Efikasi Diri - Widya, Laurentcia Noviafta; Sa'dijah, Cholis; Chandra, Tjang Daniel (Jurnal Paedagogy, 2023)
This research analyzes students' critical thinking abilities in solving Minimum Competency Assessment (AKM) questions by reviewing students' mathematical self-efficacy. This research used a descriptive method with a qualitative approach. The research subjects were 52 class VIII students at SMPK Mardi Wiyata Malang. This research instrument used AKM test sheets and mathematical self-efficacy questionnaires, which are then analyzed using an interactive model. This research showed that students with low self-efficacy abilities fulfill the indicators of interpretation, inference, evaluation, and explanation. Meanwhile, students with moderate self-efficacy fulfill the indicators of interpretation, inference, evaluation, explanation, and self-regulation. Students with high self-efficacy fulfill all indicators of critical thinking, namely interpretation, analysis, inference, evaluation, explanation, and self-regulation.